The Influence of Dance Learning on The Development of Self-Confidence in Children Aged 5-6 Years at RA Khairu Ummah, Purwodadi Village, Sunggal District, Deli Serdang Regency, Academic Year 2022/2023 - Annisa, Rizky; Damanik, Suri Handayani (MultiTech Publisher, 2023)
The study aimed to explain that there was a significant effect of learning dance on the self-confidence of children aged 5-6 years at RA Khairu Ummah Sunggal for the 2022/2023 Academic Year. The type of research used in this research is quantitative research using experimental methods. The results of the hypothesis test,